Pengaruh Expressed Emotion, Self-Stigma terhadap Regulasi Emosi pada Penyintas Bipolar dari Bipolar Care Indonesia - Yeny Duriana Wijaya; Mikaela Berliyana Alitani; Nadia Khairani (SENTRI: Jurnal Riset Ilmiah, 2025)
The purpose of this study was to find out whether there is an influence between self-stigma and emotional expression on emotion regulation in bipolar survivors. Bipolar is a psychological disorder in which the sufferer feels symptoms of emotional disorders that are significant enough to indicate a labile emotional state.  If bipolar survivors have a negative self-stigma against themselves, it will affect the emotional state of bipolar. Likewise, if there is a high expression of emotions from the family, it will also affect the emotional state. High emotional expression is indicated by the presence of critical, threatening, or overly attentional behavior. This also has a bad impact on bipolar survivors. The results of this study were measured using SASS (Stigtma And Stigma Scale) to measure self-stigma, BDSEE (Brief Dyadic Scale of Expressed Emotion) for emotional expression and Emotion Regulation Questionnaire (ERQ) to measure emotion regulation. The results of the data analysis showed that there was no significant relationship between self-stigma and emotion regulation with a significance value of 0.361 (0.05) so the hypothesis was rejected. Meanwhile, the variables of emotion expression and emotion regulation showed a significant relationship, namely with a significance of 0.033 (<0.05), thus indicating that the hypothesis was accepted.  Other results showed that the independent variables, namely self-stigma and emotional expression, had a significant relationship with a significance of 0.014 (<0.05). It can be concluded that self-stigma does not affect emotion regulation in bipolar survivors while emotion expression affects emotion regulation in bipolar survivors.